Child health psychology - Turner-Cobb, Julie M.
With a perspective designed to both inform and to challenge, this stimulating textbook introduces students to the central relevance and many applications of child health psychology. --
Keywords: Pediatrics; Sick children; Psychology, Child; Adaptation, Psychological; Child Welfare; Quality of Life; Stress, Psychological; Pediatrics; Sick children; Gesundheitspsychologie; Kind